Innovation activity in the SMEs: What factors do have effect? - Esa Storhammar; Timo Tohmo (European Regional Science Association (ERSA), 2010)
The aim of this study is to clarify what factors affect the innovation activity of small and medium-sized enterprises (SMEs), and especially the effect of regional factors. Innovations are seen as central phenomena on both micro and macro levels in economy. However, we know little about the formation, development and diffusion of innovations in different milieus. The different types of branch and enterprise structure might be the essential factor that accounts for regional differences in innovation activities. Many studies show remarkable differences between branches. Additionally, the resources of firms give an unequal starting point for innovation activities. Our study observed that the differences between regions were smaller than anticipated. It also found the innovation profiles in different areas to be fairly convergent.
Keywords: O31; 330; innovation; innovation activity; innovation strategy; SMEs; local milieu; interaction